2004
DOI: 10.1111/j.1365-2362.2004.01334.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of effects of rofecoxib on platelet function in an in vitro model of thrombosis with circulating human blood

Abstract: We conclude that under our experimental conditions, rofecoxib diminished platelet aggregation induced by different agonists and inhibited platelet-mediated thrombogenesis in an in vitro model of thrombosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…Our findings are consistent with Kumari's results [22]. To demonstrate that at this local level the TLR4-MyD88-NF-kB signaling pathway is functional, we investigated MCP-1, TNF- α , IL-1 β , and sICAM-1 levels in the serum of apoE-/- mice, since these are known to be produced through the TLR4-MyD88-NF-kB-dependent pathway [23]. We found that all four were significantly increased in CMS mice, consistent with the expression of TLR4, MyD88, and NF-kB.…”
Section: Discussionsupporting
confidence: 89%
“…Our findings are consistent with Kumari's results [22]. To demonstrate that at this local level the TLR4-MyD88-NF-kB signaling pathway is functional, we investigated MCP-1, TNF- α , IL-1 β , and sICAM-1 levels in the serum of apoE-/- mice, since these are known to be produced through the TLR4-MyD88-NF-kB-dependent pathway [23]. We found that all four were significantly increased in CMS mice, consistent with the expression of TLR4, MyD88, and NF-kB.…”
Section: Discussionsupporting
confidence: 89%
“…Celecoxib reduced polyp burden in patients with familial adenomatous polyposis by about 30% in a 6-month randomized controlled clinical trial and was approved by the FDA for use in the prevention of colorectal polyps in these patients [10]. While the reduced gastrointestinal toxicity of COX-2-selective inhibitors favors their use, recent findings suggest that certain COX-2 inhibitors, like rofecoxib and possibly valdecoxib, increase the relative risk of cardiovascular morbidity in some persons [11, 12]. …”
Section: Role Of Nsaids and The Chemoprevention Of Crcmentioning
confidence: 99%
“…Although this binding mode has to be considered nonproductive, as it is not viable for catalysis, it is in consonance with the finding from site-directed mutagenesis experiments that an arginine at position 120 is not critical for substrate binding in PGHS-2 [91] unlike PGHS-1 for which this positively charged amino acid is a major determinant for binding of both AA [88] and many NSAIDs [92]. Moreover, this unexpected positioning of the carboxylate has also been found for diclofenac which, in its complex with PGHS-2, shows its carboxylic acid similarly coordinated to both Tyr-385 and Ser-530 [93].…”
Section: Structural Overview Of Pghsmentioning
confidence: 91%
“…Incidentally, acetylation of Ser-516 (the equivalent of Ser-530 in PGHS-1) by ASA, or mutation of this residue to methionine, does not greatly affect the binding and inhibitory properties of NS-398, as opposed to meclofenamic acid or diclofenac, which are potent inhibitors of PGHS-2 but inhibit neither ASA-PGHS-2 nor the Ser-516AEMet [112] and Ser-516AEAla PGHS-2 mutant enzymes. Interestingly, this latter mutation was also shown to eliminate time-dependent inhibition by nimesulide but not competitive inhibition [93], possibly indicating a role for the side chain of this serine in inhibition by this compound. If this is the case, the orientation that places the nitro group inside the substrate channel would be preferable although a bridging water molecule would probably be necessary to mediate a hydrogen bonding interaction between the nitro moiety of the drug and the hydroxyl group of Ser-516.…”
Section: Experimental Support For the Proposed Binding Modementioning
confidence: 97%
See 1 more Smart Citation